2008
DOI: 10.1677/joe-07-0647
|View full text |Cite
|
Sign up to set email alerts
|

Orchidectomy increases the formation of non-endothelial thromboxane A2 and modulates its role in the electrical field stimulation-induced response in rat mesenteric artery

Abstract: The aim of this study was to analyze whether endogenous male sex hormones influence the release of thromboxane A 2 (TXA 2 ) and its role in the electrical field stimulation (EFS)-induced response, as well as the mechanism involved. For this purpose, endothelium-denuded mesenteric arteries from control and orchidectomized male Sprague-Dawley rats were used to measure TXA 2 release; EFS-induced response, nitric oxide (NO), norepinephrine (NA), and prostaglandin (PG) I 2 release were also measured in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 54 publications
3
19
0
Order By: Relevance
“…We observed that orchidectomy decreased the EFS-induced contraction, which is in agreement with that observed in mesenteric artery from 5 months-post-orchidectomized rats [13] in which the release of NA was not modified [18]. DHA-supplemented diet reversed the reduction in EFS-induced contractile response caused by orchidectomy.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We observed that orchidectomy decreased the EFS-induced contraction, which is in agreement with that observed in mesenteric artery from 5 months-post-orchidectomized rats [13] in which the release of NA was not modified [18]. DHA-supplemented diet reversed the reduction in EFS-induced contractile response caused by orchidectomy.…”
Section: Discussionsupporting
confidence: 89%
“…In this regard, the contractile response induced by potassium depolarization was not altered by a DHA diet in hypertensive rats [37]. Although, we have previously reported that the orchidectomy did not modify the release of neuronal NO [13] and NA [18], it would have been desirable to determine the neurogenic release of NA and NO. The authors acknowledge this limitation of the current study and, because of the intriguing and complex interactions among the different factors, this issue will be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that TXA 2 is one of the most important vasoconstrictor prostanoids produced by the vascular wall that may participate in vascular dysfunction associated with cardiovascular risk factors [36][38]. We have already demonstrated that the release of TXA 2 was increased 5 months post-orchidectomy in mesenteric artery [9], [10], [19], probably as consequence of increased oxidative stress observed in these experimental conditions. To ascertain whether the release of TXA 2 also depends on the time lapsed since the gonadal function is lost, its release was also analyzed in vessels from 6 weeks post-orchidectomized rats.…”
Section: Discussionmentioning
confidence: 62%
“…These issues, as well as different mechanisms of action by which testosterone causes vasodilation were reviewed by Jones [7], In this regard, previous studies from our group have demonstrated an increase in the production of superoxide anion [8], prostanoids, such as thromboxane A 2 (TXA 2 ) [9], [10] and prostaglandin E 2 (PGE 2 ) [11] five months post-orchidectomy. Concerning the effect of androgens on endothelial NO release, most of studies were carried out in endothelial cells culture showing an increased release [12][14].…”
Section: Introductionmentioning
confidence: 99%